2021
DOI: 10.3390/agriculture11060542
|View full text |Cite
|
Sign up to set email alerts
|

Application of Plant Extracts in Micropropagation and Cryopreservation of Bleeding Heart: An Ornamental-Medicinal Plant Species

Abstract: Lamprocapnos spectabilis (L.) Fukuhara (bleeding heart) is valued both in the horticultural and pharmaceutical markets. Despite its great popularity, information on the in vitro tissue culture technology in this species is limited. There is also little knowledge on the application of plant extracts in the tissue culture systems of plants other than orchids. The aim of this study is to compare the utility of traditional plant growth regulators (PGRs) and natural extracts—obtained from the coconut shreds, as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…Wang et al [52] found that metal-based nanoparticles can cause damage to roots or be absorbed by plant roots, triggering oxidative stress, which in turn hampers root growth and nutrient uptake. The obtained results also correspond with the findings of Kulus and Miler [53], who described a cultivar-specific reaction of bleeding heart 'Gold Heart' and 'White Gold' shoot tips, both in terms of survival and morphogenesis, to cryopreservation protocols based on natural plant extracts.…”
Section: Plos Onesupporting
confidence: 89%
“…Wang et al [52] found that metal-based nanoparticles can cause damage to roots or be absorbed by plant roots, triggering oxidative stress, which in turn hampers root growth and nutrient uptake. The obtained results also correspond with the findings of Kulus and Miler [53], who described a cultivar-specific reaction of bleeding heart 'Gold Heart' and 'White Gold' shoot tips, both in terms of survival and morphogenesis, to cryopreservation protocols based on natural plant extracts.…”
Section: Plos Onesupporting
confidence: 89%
“…Over the years, extracts of various origins have been added to in vitro propagation media (Molnár et al, 2011;Venkatachalam et al, 2015), but little attention has been paid to their use in cryopreservation. In a study by Kulus and Miler (2021), fresh aquatic extracts obtained from coconut shreds, oat, rice, and sesame seeds were added into the preculture medium during cryopreservation via the encapsulation-vitrification of two bleeding heart cultivars. It was found that coconut extract, abundant in endogenous cytokinins and simple sugars, stimulated more intensive shoot proliferation and development aer the rewarming of explants than the extract-free control did.…”
Section: Plant Extracts and Nanoparticles (Nps) In Improving Cryopres...mentioning
confidence: 99%
“…The cell and tissue culture techniques have some important advantages in agriculture, horticulture, and other important aromatic crop plants. Aromatic and medicinal plants represent good choices for investigation concerning the study of growth and morphogenesis of plant tissue cultures by adding different proportion of compounds, hormones or extracts [15,16].…”
Section: Introductionmentioning
confidence: 99%